Kuasa Politik Negara Dalam Proses Degradasi Lingkungan Pada Kawasan Hutan Yawila Desa Eka Pata, Kabupaten Sumba Barat Daya - Bulu Ladi, Fredirikus; Giri Wiloso, Pamerdi (Jurnal Lazuardi, 2023)
This research aimed to describe the Politic Power of Nation toward the community’s local custom in Eka Pata Village, middle Wewewa, South West Sumba Regency. The politic power passed by the Eka Pata village government, the forest polices, the polices and the authority to press the leaders of Lobo ethnic in the hill of Yawila mountain forest. These actors press and also terror the leaders of group so that they don’t rival about the group protection forest destruction. This research used qualitative approach, the data collection technique is by interview and documentation. The informers in this research consist of ex- second village chief, the leader of Lobo ethnic, local custom society, and the villagers of second village who manage the area in Yawila forest. The research result showed that Yawila forest have had degradation because of illegal loggings that continues are done by society groups of second village in Eka Pata village since 2019 until at this moment. The society in second village doing the plantation activity because is given permission by forest UPTD of South West Sumba Regency in order to plant the local crops. In fact, the environmental damage does not give impact toward the increasing family economic welfare for the villagers in second village who doing the plantation activity in that protection forest. Even, the hereditary impact that resulted is very bigger namely the local community villagers who are there losing the resource of herbal drug, the forest and water become damaged. Beside that, it will give the benefit conflict in the future between society groups and Marapu local custom community.